Investigation of the nuclear structure of 84-108Mo isotopes using Skyrme-Hartree-Fock method - Alzubadi, Ali A. (Iraqi Journal of Physics, 2019)
Over the last few decades the mean field approach using selfconsistent Haretree-Fock (HF) calculations with Skyrme effective interactions have been found very satisfactory in reproducing nuclear properties for both stable and unstable nuclei. They are based on effective energy-density functional, often formulated in terms of effective density-dependent nucleon–nucleon interactions. In the present research, the SkM, SkM*, SI, SIII, SIV, T3, SLy4, Skxs15, Skxs20 and Skxs25 Skyrme parameterizations have been used within HF method to investigate some static and dynamic nuclear ground state proprieties of 84-108Mo isotopes. In particular, the binding energy, proton, neutron, mass and charge densities and corresponding root mean square radius, neutron skin thickness and charge form factor are calculated by using this method with the Skyrme parameterizations mentioned above. The calculated results are compared with the available experimental data. Calculations show that the Skyrme–Hartree–Fock (SHF) theory with above force parameters provides a good description on Mo isotopes.